THE INFLUENCE OF SOCIAL MEDIA ON CUSTOMER PURCHASE INTENTIONS FOR GREEN FAST FASHION PRODUCTS - Pakpahan, Arnolt Kristian; Chandra, Kristian; Magetsari, Ovy Noviati Nuraini; Nilawati, Yuana Jatu (Universitas Muhammadiyah Tangerang, 2025)
This study aims to analyze the influence of social media marketing, green product knowledge, and attitudes towards green products on interest and purchase decisions of eco-friendly products among millennials. This study is important because there is still a limited understanding of the factors that drive the adoption of green products, especially in the fashion industry which is facing sustainability trends. The research uses an associative qualitative approach by analyzing consumer perceptions through in-depth interviews and literature studies. The results of the study showed that: (1) exposure to information on social media, (2) understanding of the characteristics of green products, and (3) pro-environmental attitudes collectively influenced buying interest. These findings make a theoretical contribution by expanding the Theory of Planned Behavior (TPB) model in the context of green fashion, as well as practical contributions to: (a) marketers—in designing educational digital campaigns, and (b) governments—as the basis for sustainable consumer education policies. The implication is that fashion businesses need to present green product information in a transparent and easily accessible manner to increase consumer appeal.